Penerapan Sistem Informasi Manajemen Daerah dan Kompetensi Sumber Daya Manusia Terhadap Kualitas Laporan Keuangan Pemda - Usman (Program Studi S1 Akuntansi Jurusan Akuntansi, Fakultas Ekonomi Universitas Negeri Gorontalo, 2022)
This study aims to determine the effect of implementing a regional management information system (SIMDA) and human resource competence on the quality of local government financial reports in Gorontalo City. the method used in this research is a quantitative research method. The number of samples in this study were 68 respondents who were determined based on random sampling. The source of the data used is primary data obtained from the results of distributing questionnaires to all employees who are directly involved in the preparation of financial reports in the city of Gorontalo. The data analysis technique used in this research is multiple linear regression analysis with partial test and simultaneous test. The results of this study indicate that partially the application of the regional management information system and human resource competence have a significant effect on the quality of the financial statements of the Gorontalo city government. This result is evidenced by the coefficient of determination of 51.1%.